Vocational Knowledge Testing of a Deaf and Hard of Hearing Population - Fitzsimmons, G.; Butson, Sarah (Canadian Journal of Counselling and Psychotherapy, 2011)
A total of forty-eight adults with either complete or partial hearing impairment were involved in a study to investigate the efficacy of a test of vocational knowledge to assist in decisionmaking and career-planning for the deaf and hard of hearing. The twenty-one women and twenty-seven men ranging in age from eighteen to fifty-three years were clientele of an Edmonton, Alberta, employment centre for those with special needs. All participants were administered a test adapted from the Scale of Vocational Maturity using a questionnaire based on Holland's (1975) classification of occupations. Results indicated that the type of school attended by the client influenced vocational knowledge scores more than any other factor considered. Those who had attended schools for hearing populations demonstrated significantly more knowledge concerning specific occupations than those who had attended schools for the deaf. Women scored higher than men in knowledge related to occupations in the "Artistic" category. No differences due to sex were evident for values related to sex-stereotyping of jobs. High scores across the entire population tested on attitude towards sex-roles indicated a high degree of acceptance of the capability of wither sex to perform any of the occupation considered. Inter-item reliability was apparent as correlations between scores of knowledge of specific occupations and overall occupational scores were generally positive and highly significant. When occupation class scores for each individual were normed for the population in the present study and graphed on a profile, results from the objective test compared favourably with the counsellor's personal appraisal of the client's overall vocational knowledge, demonstrating a high degree of external validity.